When Civil and Penal are Mixed Up: Hybrid and Discontinuous Youth’ Judicial Trajectories in France - Teillet, Guillaume (Swiss Journal of Sociocultural Anthropology, 2020)
On the basis of an ethnographic survey about young people followed by the Youth Judicial Protection Service (Projection judiciaire de la jeunesse, PJJ) in France, this article deals with the effects of the duality of juvenile justice (civil and penal) on the scale of their trajectories. Upstream from prosecutions, placements under child protection are one of the sequences of the disorders’ chain of production. From the break marked by the first penal placement, the PJJ supervising leans diversely on civil cares, between hybridization of judicial registers, overlap, and definition of respective perimeters. Further down penal trajectories and beyond their majority, the return of these young people towards civil protectional channels turns out to be uncertain, nay compromised.